2000
DOI: 10.1302/0301-620x.82b3.0820416
|View full text |Cite
|
Sign up to set email alerts
|

The depressor function of biceps on the head of the humerus in shoulders with tears of the rotator cuff

Abstract: We investigated the function of biceps in 18 patients (19 shoulders) with lesions of the rotator cuff. Their mean age was 59 years. Another series of 18 patients (19 shoulders) with normal rotator cuffs as seen on MRI acted as a control group. Their mean age was 55 years. A brace was used to maintain contraction of biceps during elevation. Anteroposterior radiographs were obtained with the arm elevated at 0°, 45° and 90° with and without contraction of biceps. The distance between the centre of the head of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 9 publications
1
44
0
2
Order By: Relevance
“…Specifically, a cadaveric study examined the role of the long head of the biceps in the presence of supraspinatus and infraspinatus tears [23] and found that loading of the long head of the biceps tendon decreased humeral head translations. Results from a clinical EMG study suggested that the long head of the biceps tendon assists the supraspinatus with humeral head depression during shoulder elevation [8]. However, due to confounding variables in clinical and cadaver studies, it is difficult to determine true cause and effect relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a cadaveric study examined the role of the long head of the biceps in the presence of supraspinatus and infraspinatus tears [23] and found that loading of the long head of the biceps tendon decreased humeral head translations. Results from a clinical EMG study suggested that the long head of the biceps tendon assists the supraspinatus with humeral head depression during shoulder elevation [8]. However, due to confounding variables in clinical and cadaver studies, it is difficult to determine true cause and effect relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The long head of the biceps tendon crosses the shoulder and may serve as an important joint stabilizer, particularly in the presence of cuff tears; however, its role in joint stability remains controversial. Specifically, some believe that it provides minimal stability at the shoulder [11,27], while others believe it serves mainly as a humeral head depressor, assisting the supraspinatus [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the LHB tendon is an active stabilizer of the glenohumeral joint (Warner et al 1995) and an active depressor of the humeral head in cuff tear shoulders (Kido et al 2000), the widened LHB tendon may be due to hyperactivity of the biceps muscle in order to compensate for the functional deficit caused by rotator cuff tear. An EMG study by Kido et al (1998) demonstrated that only onethird of patients with rotator cuff tears showed increased activity of the biceps during arm elevation compared to that in subjects without rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…Since the LHB is a stabilizer (Kumar et al 1989, Itoi et al 1994) and depressor (Warner et al 1995, Kido et al 2000 of the humeral head, the widened LHB tendon in cuff tear shoulders may be a hypertrophic change to compensate for the functional loss of the cuff (Matsen et al 1998). An et al (1991) reported that tendon cross-sectional area (CSA) correlated well with the physiological CSA (PCSA) of associated muscles.…”
mentioning
confidence: 99%
“…4,41,42,45,53,78 It is difficult to determine the extent to which biceps surgery will affect shoulder function, because the role of the biceps at the shoulder is not fully understood. Maintaining the biceps muscle length-tension relationship and the axis of the biceps muscle is thought to be important for preserving biceps function at the shoulder.…”
mentioning
confidence: 99%